Peran Pemerintah Daerah Dalam Melestarikan Adat Maccerang Manurung Di Desa Kaluppini Kabupaten Enrekang - Trisandi, Risna; Razak, Andi Rosdianti; Usman, Jaelan (Universitas Muhammadiyah Makassar, 2021)
This study purposed to find out the existence of Mccerang Manurung Custom and the role of the Regional Government in the preservation of Maccerang Manurung Custom in Kaluppini Village, Enrekang Regency. This study used qualitative with the type was qualitative descriptive research type with 8 informants. Data collection techniques were observation, interview, documentation. The results of this study indicated that the role of the government in terms of being the activator was not yet maximal in implementation because there was still much to be done by the government as well as having to start the process of implementing the agenda and not only from the community and from the village but all the people of Kaluppuni Village because it should be maximal in preserving maccerang manurung custom because it was a culture of local heritage, a picture of the customs of the people of South Sulawesi, especially the people of Enrekang district.